Theoretical aspects and basic principles of financial analysis - Vučičević Dušan (Škola Biznisa, 2012)
In economic business and life of an enterprise - a company, whether an economic size or an economic result is good, very good, or, rather, weak can hardly be marked and it is always done by comparison: with the investment of certain inputs, with the results of businesses, with achievements in the past, with the planned size and results (with needs), etc. Performance indicators, financial analysis, correlation and understanding of them are of great importance in economy and give orientation for shareholders, managers, experts. Understandably, there are a lot of parameters (rates, ratios). In this paper, attention is paid to the following financial ratios and indicators, namely: liquidity ratios, activity indicator, profitability ratios and indicators of financial structure and financing. All of them are used in financial analysis. All this was done in order to identify an appropriate set of criteria for evaluating company performance, which will serve to identify the success of the company. The text focuses on theoretical aspects and basic principles of financial analysis and preliminary selection of indicators of the efficiency of business operations.